# The 42isms of vogonpoet

WARNING! This may well be one of the most pointless and dull entries in the entire guide.

Combinational42ology:

1 x (74 - 32) x 1 = 42

1! x (74 - 32) x 1 = 42

1 x (74 - 32) x 1! = 42

1! x (74 - 32) x 1! = 42

1 x (74 - 32) / 1 = 42

1! x (74 - 32) / 1 = 42

1 x (74 - 32) / 1! = 42

1! x (74 - 32) / 1! = 42

1^7 + 43 - (2 x 1) = 42

1!^7 + 43 - (2 x 1) = 42

1^7 + 43 - (2 x 1!) = 42

1!^7 + 43 - (2 x 1!) = 42

1^7 + 43 - (2! x 1) = 42

1!^7 + 43 - (2! x 1) = 42

1^7 + 43 - (2! x 1!) = 42

1!^7 + 43 - (2! x 1!) = 42

(1^7 + 43 - 2) / 1 = 42

(1!^7 + 43 - 2) / 1 = 42

(1^7 + 43 - 2) / 1! = 42

(1!^7 + 43 - 2) / 1! = 42

(1^7 + 43 - 2!) / 1 = 42

(1!^7 + 43 - 2!) / 1 = 42

(1^7 + 43 - 2!) / 1! = 42

(1!^7 + 43 - 2!) / 1! = 42

(1 x 7) x (4 x 3) / (2 x 1) = 42

(1! x 7) x (4 x 3) / (2 x 1) = 42

(1 x 7) x (4 x 3) / (2 x 1!) = 42

(1! x 7) x (4 x 3) / (2 x 1!) = 42

(1 x 7) x (4 x 3) / (2! x 1) = 42

(1! x 7) x (4 x 3) / (2! x 1) = 42

(1 x 7) x (4 x 3) / (2! x 1!) = 42

(1! x 7) x (4 x 3) / (2! x 1!) = 42

(1 x 7) x (4 x 3) / (2 / 1) = 42

(1! x 7) x (4 x 3) / (2 / 1) = 42

(1 x 7) x (4 x 3) / (2 / 1!) = 42

(1! x 7) x (4 x 3) / (2 / 1!) = 42

(1 x 7) x (4 x 3) / (2! / 1) = 42

(1! x 7) x (4 x 3) / (2! / 1) = 42

(1 x 7) x (4 x 3) / (2! / 1!) = 42

(1! x 7) x (4 x 3) / (2! / 1!) = 42

17 + 4! + 3 - (2 x 1) = 42

17 + 4! + 3 - (2 x 1!) = 42

17 + 4! + 3 - (2! x 1) = 42

17 + 4! + 3 - (2! x 1!) = 42

17 + 4! + 3 - (2 / 1) = 42

17 + 4! + 3 - (2 / 1!) = 42

17 + 4! + 3 - (2! / 1) = 42

17 + 4! + 3 - (2! / 1!) = 42

(1 x 7) x ((4! / 3) - 2) x 1 = 42

(1! x 7) x ((4! / 3) - 2) x 1 = 42

(1 x 7) x ((4! / 3) - 2) x 1! = 42

(1! x 7) x ((4! / 3) - 2) x 1! = 42

(1 x 7) x ((4! / 3) - 2!) x 1 = 42

(1! x 7) x ((4! / 3) - 2!) x 1 = 42

(1 x 7) x ((4! / 3) - 2!) x 1! = 42

(1! x 7) x ((4! / 3) - 2!) x 1! = 42

(1 x 7) x ((4! / 3) - 2) / 1 = 42

(1! x 7) x ((4! / 3) - 2) / 1 = 42

(1 x 7) x ((4! / 3) - 2) / 1! = 42

(1! x 7) x ((4! / 3) - 2) / 1! = 42

(1 x 7) x ((4! / 3) - 2!) / 1 = 42

(1! x 7) x ((4! / 3) - 2!) / 1 = 42

(1 x 7) x ((4! / 3) - 2!) / 1! = 42

(1! x 7) x ((4! / 3) - 2!) / 1! = 42

(1 x 7) x ((4! / 3!) + 2) x 1 = 42

(1! x 7) x ((4! / 3!) + 2) x 1 = 42

(1 x 7) x ((4! / 3!) + 2) x 1! = 42

(1! x 7) x ((4! / 3!) + 2) x 1! = 42

(1 x 7) x ((4! / 3!) + 2!) x 1 = 42

(1! x 7) x ((4! / 3!) + 2!) x 1 = 42

(1 x 7) x ((4! / 3!) + 2!) x 1! = 42

(1! x 7) x ((4! / 3!) + 2!) x 1! = 42

(1 x 7) x ((4! / 3!) + 2) / 1 = 42

(1! x 7) x ((4! / 3!) + 2) / 1 = 42

(1 x 7) x ((4! / 3!) + 2) / 1! = 42

(1! x 7) x ((4! / 3!) + 2) / 1! = 42

(1 x 7) x ((4! / 3!) + 2!) / 1 = 42

(1! x 7) x ((4! / 3!) + 2!) / 1 = 42

(1 x 7) x ((4! / 3!) + 2!) / 1! = 42

(1! x 7) x ((4! / 3!) + 2!) / 1! = 42

17 + (4 x 3!) + 2 - 1 = 42

17 + (4 x 3!) + 2 - 1! = 42

17 + (4 x 3!) + 2! - 1 = 42

17 + (4 x 3!) + 2! - 1! = 42

(1 x 7) x (sqrt4 x 3) x (2 - 1) = 42

(1! x 7) x (sqrt4 x 3) x (2 - 1) = 42

(1 x 7) x (sqrt4 x 3) x (2 - 1!) = 42

(1! x 7) x (sqrt4 x 3) x (2 - 1!) = 42

(1 x 7) x (sqrt4 x 3) x (2! - 1) = 42

(1! x 7) x (sqrt4 x 3) x (2! - 1) = 42

(1 x 7) x (sqrt4 x 3) x (2! - 1!) = 42

(1! x 7) x (sqrt4 x 3) x (2! - 1!) = 42

(17 x sqrt4) + 3! + 2 x 1 = 42

(17 x sqrt4) + 3! + 2! x 1 = 42

(17 x sqrt4) + 3! + 2 x 1! = 42

(17 x sqrt4) + 3! + 2! x 1! = 42

((1 + 7) x 4) + 3^2 + 1 = 42

((1! + 7) x 4) + 3^2 + 1 = 42

((1 + 7) x 4) + 3^2 + 1! = 42

((1! + 7) x 4) + 3^2 + 1! = 42

((1 + 7) x 4) + 3^2! + 1 = 42

((1! + 7) x 4) + 3^2! + 1 = 42

((1 + 7) x 4) + 3^2! + 1! = 42

((1! + 7) x 4) + 3^2! + 1! = 42

(-1 + 7) x (4 + 3) x (2 - 1) = 42

(-1! + 7) x (4 + 3) x (2 - 1) = 42

(-1 + 7) x (4 + 3) x (2 - 1!) = 42

(-1! + 7) x (4 + 3) x (2 - 1!) = 42

(-1 + 7) x (4 + 3) x (2! - 1) = 42

(-1! + 7) x (4 + 3) x (2! - 1) = 42

(-1 + 7) x (4 + 3) x (2! - 1!) = 42

(-1! + 7) x (4 + 3) x (2! - 1!) = 42

(-1 + 7) x ((4! / 3!) + 2 + 1) = 42

(-1! + 7) x ((4! / 3!) + 2 + 1) = 42

(-1 + 7) x ((4! / 3!) + 2 + 1!) = 42

(-1! + 7) x ((4! / 3!) + 2 + 1!) = 42

(-1 + 7) x ((4! / 3!) + 2! + 1) = 42

(-1! + 7) x ((4! / 3!) + 2! + 1) = 42

(-1 + 7) x ((4! / 3!) + 2! + 1!) = 42

(-1! + 7) x ((4! / 3!) + 2! + 1!) = 42

1^7 + 4 + (3!)^2 + 1 = 42

1!^7 + 4 + (3!)^2 + 1 = 42

1^7 + 4 + (3!)^2 + 1! = 42

1!^7 + 4 + (3!)^2 + 1! = 42

1^7 + 4 + (3!)^2! + 1 = 42

1!^7 + 4 + (3!)^2! + 1 = 42

1^7 + 4 + (3!)^2! + 1! = 42

1!^7 + 4 + (3!)^2! + 1! = 42

sqrt (1743 + 21) = 42